Impact of democratic/non-democratic regimes on foreign direct investment in Pakistan: Pre and post September 11, 2001 scenarios - Tahir Nawaz; Masood Amjad Khan; Muhammad Akbar Ali Shah; Muhammad Aleem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
In this study the impact of democratic and non-democratic regime (pre and post September 11, 2001seenarios) on foreign direct investment in Pakistan have been investigated using quarterly data over the period of 1976Q1 to 2006Q4. Stepwise regression, Box-Jenkins methodologies have been applied initially then GARCH-type models are used to counter the problems of auto-correlation and ARCH effect and to model the conditional variance of FDI. It is found that foreign direct investment in Pakistan mainly depends upon on the past trends, as higher order auto-regressive terms are statistically significant. It has also been observed that the volatility shocks are quite persistent and take a long time to die out. September 11, 2001incident and thereafter war on terror has increased the conditional volatility of foreign direct investment and has statistically significant impact while FDI was not volatile before the September, 11, 2001. CPI plays a significant role to decrease conditional volatility. One interesting finding of this study is that the impact of Non-Democratic regime before September, 11 scenario is statistically significant and severely bad on foreign direct investment but with the inclusion of observations of post September, 11 the variable becomes insignificant
Keywords: 330; Box and Jenkins Methodology; GARCH Model; Auto-correlation; ARCH Effect; Volatility; Politisches System; Auslandsinvestition; Ausländisch; Volatilität; ARCH-Modell; Korrelation; Schätzung; Pakistan